2021
DOI: 10.1038/s41467-021-22378-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-structural carbohydrates mediate seasonal water stress across Amazon forests

Abstract: Non-structural carbohydrates (NSC) are major substrates for plant metabolism and have been implicated in mediating drought-induced tree mortality. Despite their significance, NSC dynamics in tropical forests remain little studied. We present leaf and branch NSC data for 82 Amazon canopy tree species in six sites spanning a broad precipitation gradient. During the wet season, total NSC (NSCT) concentrations in both organs were remarkably similar across communities. However, NSCT and its soluble sugar (SS) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 67 publications
0
45
1
Order By: Relevance
“…Within the rainforest, the regions with the strongest sensitivity to VPD lie at lower elevations (Figure 5i,j), which have greater soil moisture and greater access to groundwater (e.g., from partial inundation). In these low-lying environments, we explain the vegetation sensitivity to VPD by the fact that plants acclimated to plentiful soil water supplies have developed lower resistance to xylem embolism (Oliveira et al, 2019;Signori-Müller et al, 2021), and are thus sensitive to VPD increases, since (partial) stomatal closure occurs at high VPD, causing a rise of LST/T air .…”
Section: Discussionmentioning
confidence: 99%
“…Within the rainforest, the regions with the strongest sensitivity to VPD lie at lower elevations (Figure 5i,j), which have greater soil moisture and greater access to groundwater (e.g., from partial inundation). In these low-lying environments, we explain the vegetation sensitivity to VPD by the fact that plants acclimated to plentiful soil water supplies have developed lower resistance to xylem embolism (Oliveira et al, 2019;Signori-Müller et al, 2021), and are thus sensitive to VPD increases, since (partial) stomatal closure occurs at high VPD, causing a rise of LST/T air .…”
Section: Discussionmentioning
confidence: 99%
“…tolerating low Ψ) among non-succulent plants ( Lenz et al , 2006 ; Blackman et al , 2010 ). Many arid-adapted non-succulents respond to drought by lowering their already low TLP Ψ through physiological adjustments, primarily osmotic adjustments ( Bartlett et al , 2012 ; Turner, 2018 ; Signori-Müller et al , 2021 ). On the other hand, measurements of TLP Ψ and the closely related Ψ S (see formula in Bartlett et al , 2012 ) in drought-avoiding succulents have shown that they exhibit relatively high TLP Ψ values ( Walter and Stadelmann, 1974 ; Smith and Lüttge, 1985 ; von Willert et al , 1992 ; Donatz and Eller, 1993 ; Gotsch et al , 2021 , Preprint; Leverett et al , 2021 ); their ability to maintain high Ψ seems to relax the need for a low TLP Ψ .…”
Section: Structure and Function Of Cell Walls In Succulentsmentioning
confidence: 99%
“…The structural mechanisms responsible for enhancing the water storage capacity in trees are underpinned by the anatomical configuration of the woody tissues with both capillary storage compartments (i.e., open vessels, tracheids, fibers, intercellular spaces, and cracks) and elastic storage compartments (i.e., living parenchyma cells) likely to be relevant ( Borchert and Pockman, 2005 ; Scholz et al, 2008 ; Jupa et al, 2016 ; Kawai et al, 2021 ). Not only the anatomic features define plant water storing capacity but also the chemical compounds with osmotic activity play an essential role in plant osmotic adjustment ( Turner and Jones, 1980 ; Turner, 2018 ; Signori-Müller et al, 2021 ). The accumulation of osmotically active elements in the tissues decreases the water potential, thus enabling the maintenance of high cellular turgor potential and water retention ( Blum, 2017 ; Traversari et al, 2020 ; da Silva et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%